Tie points for manual alignment of the benthic foraminiferal δ¹⁸O record at IODP Site U1541 to LR04 - Middleton, Jenny; Gottschalk, Julia; Winckler, Gisela; Hanley, Jean; Knudsen, Carol; Farmer, Jesse R; Lisiecki, Lorraine E; Lamy, Frank (In: Middleton, J et al. (2024): Benthic foraminiferal δ¹⁸O alignments for IODP Site U1541, ODP Site 1090 and ODP Site 980-981 based on different tuning targets for the past ~3.5 Myr [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.965845, 2024)
This dataset presents user-defined tiepoints of the manual alignment of the benthic foraminiferal δ¹⁸O record at IODP Site U1541 to the benthic foraminiferal LR04 δ¹⁸O stack of Lisiecki and Raymo (2005) obtained by Middleton et al. (2024). The benthic foraminiferal δ¹⁸O record for IODP Site U1541 is based on stable isotope analyses of Cibicidoides wuellerstorfi and Cibicides kullenbergi, and was published in Middleton et al. (2024).